Problematika Pendekatan Saintifik Pada Pembelajaran PAI - Muhammad Zidane Ansyari; Urwatul Wusqo Nur Salsabila; Muhammad Khairul Rijal (Institut Agama Islam Negeri (IAIN) Samarinda, 2018)
Education has become a container of high complexity. Beyond being given a great mandate for man to know and live independently of his life, as well as to benchmark the progress of civilization in the future nation. Knowing the degree of complexity that it bears, therefore, is a necessity for educational participants to innovate in time and again. This is not something that concerns Islamic religious education. Within its delivery there isa realm that is not logistically acceptable, and it can be dictated through a scientific approach by the amtsal method.